„Dissoziation und Status der Ich-Rolle in den Liedern Suchensinns“ - Egidi, Margreth (Neue Forschungen zur mittelhochdeutschen Sangspruchdichtung (ZfdPh 119, Sonderh.))

Nonlinear Polariton Pulse Propagation in Bulk Semiconductors - Meier, Torsten; Förstner, J.; Knorr, A.; Kuckenburg, S.; Koch, S.W.; Giessen, H.; Linden, S.; Kuhl, J. (physica status solidi (b))
Nonlinear propagation of optical pulses through an extended bulk semiconductor is investigated using the coupled semiconductor Maxwell-Bloch equations including excitation induced correlations. For short pulse excitation around the exciton resonance, the theory describes the development of polariton beats and their suppression at increasing input pulse intensities due to the coupling of single exciton states to the Coulomb-correlated continuum of two-exciton states. A comparison of the theoretical results with experimental observations for CdSe bulk material is presented.

Analysis of Excitonic Absorption Changes Induced by Incoherent Exciton and Electron-Hole-Pair Populations - Meier, Torsten; Koch, S.W. (physica status solidi (b))
The density-dependent absorption in the presence of incoherent occupations of excitons and electron–hole pairs is analyzed including many-body correlations represented by exciton to two-exciton transitions. At low temperatures the exciton resonance is bleached and shifts to higher energies with increasing density. For higher temperature, the blue shift disappears and pure bleaching is obtained.

Propagation of Coulomb-Correlated Electron-Hole Pairs in Semiconductors with Correlated and Anticorrelated Disorder - Meier, Torsten; Thomas, P.; Varga, I.; Lemm, T.; Golub, J.E.; Maschke, K.; Koch, S.W. (physica status solidi (b))
Local ultrafast optical excitation of electron–hole pairs in disordered semiconductors provides the possibility to observe experimentally interaction-assisted propagation of correlated quantum particles in a disordered environment. In addition to the interaction driven delocalization known for the conventional single-band TIP-(two-interacting-particles)-problem the semiconductor model has a richer variety of physical parameters that give rise to new features in the temporal dynamics. These include different masses, correlated versus anticorrelated disorder for the two particles, and dependence on spectral position of excitation pulse.

Investigation of Disordered Semiconductor Quantum Wells by Coherent Excitation Spectroscopy - Meier, Torsten; Euteneuer, A.; Finger, E.; Stolz, W.; Thomas, P.; Koch, S.W.; Hofmann, M.; Rühle, W.W.; Hey, R.; Ploog, K.H. (physica status solidi (a))
First, we study coupling of excitons in different quantum-well islands by coherent excitation spectroscopy and find that excitons in different islands are not coherently coupled. Second, we investigate exciton and biexciton binding energies in inhomogeneously broadened (GaIn)As/Ga(PAs) multi quantum wells. A strong increase of the 1s–2s-splitting with increasing exciton localization is found, whereas the biexciton binding energy shows a very weak decrease with increasing localization.

Coulomb Memory Effects and Higher-Order Coulomb Correlations in the Excitonic Optical Stark Effect - Meier, Torsten; Brick, P.; Ell, C.; Hübner, M.; Prineas, J.P.; Khitrova, G.; Gibbs, H.M.; Sieh, C.; Jahnke, F.; Knorr, A.; Koch, S.W. (physica status solidi (a))
Differential absorption spectra of high quality InGaAs quantum wells were measured by means of pump–probe spectroscopy as a function of pump–probe delay, for different polarizations of the pulses, and different spectral detunings of the pump beam with respect to the 1s heavy-hole exciton. A clear redshift of the heavy-hole resonance is observed for large detunings and opposite circularly polarized pulses. Microscopic calculations that include not only the Hartree-Fock contribution but also higher-order Coulomb correlations reproduce the experimental findings very well. It is shown that the redshift is caused by Coulomb memory effects and is further enhanced due to the presence of the bound biexciton.

Comparison of the differential absorption obtained within a few-level model and the microscopic density-matrix theory - Meier, Torsten; Reichelt, Matthias; Sieh, C.; Koch, S.W. (physica status solidi (b))
A phenomenological multi-exciton level scheme is used to calculate the excitonic differential absorption as measured in pump and probe experiments. Numerical results are compared to those obtained by a fully microscopic density-matrix theory. For resonant excitation, optimized parameters yield qualitative agreement, but the phenomenological approach soon reaches its limit for non-resonant pumping.

Current Echoes induced by Coherent Control - Meier, Torsten; Stippler, J.; Schlichenmaier, C.; Knorr, A.; Lindberg, M.; Thomas, P.; Koch, S.W. (physica status solidi (b))
A scheme to generate an experimentally measurable current echo is proposed where current pulses are induced by a sequence of phase coherent optical pulses. Based on microscopic calculations for a one-dimensional tight-bindig model of a disordered two-band semiconductor it is predicted that excitation sequences can be taylored such that after two induced time-delayed current pulses a current echo pulse results.

Theoretical Aspects of the Optical Response of Semiconductor Surfaces - Bechstedt, F.; Pulci, O.; Schmidt, Wolf Gero (physica status solidi (a))

Zeitroman, mimetisch. Textgeschichte, Verfahren und Status von Marieluise Fleißers ›Mehlreisende Frieda Geier‹ - Süßmann, Johannes (Literatur und Leben. Stationen weiblichen Schreibens im 20. Jahrhundert. Unter Mitarbeit v. Lena Lindhoff)